Special and Differential Treatment under the World Trade Organization : Perspective on International Trade Law - Aryuni Yuliantiningsih (Universitas Kuningan, 2021)
GATT/WTO regulates the principle of special and differential treatment in part IV as a way to address international trade inequality for developing countries. This study aims to examine the theoretical and practical principles of Special and Differential (SD). The study employed a normative juridical method involving a statutory and conceptual approach. The study revealed that the SD principle theoritically aims to attain justice for developing countries. This is in line with the theory of justice from John Rawls mentioning justice as fairness. In the context of international trade, this is also in line with Frank J Garcia. Based on these theories, SD demands a different treatment betwixt developed and developing countries. Generally, the SD principle is an instrument to attain fairness in international trade. In its implementation, the SD provisions aimed at helping developing countries. This involves market access, protecting the interest of the developing countries, and flexibility and transition period. However, the latter seems hard to enforce because developed countries frequently sue developing countries to the WTO panel once the SD principles are utilized by them. GATT/WTO mengatur prinsip Special and Differential treatment dalam Bagian IV sebagai cara untuk mengatasi ketimpangan perdagangan internasional bagi negara berkembang. Artikel ini bertujuan untuk mengkaji Prinsip Special and Differential (SD) secara teoritis dan praktis. Metode penelitian yang digunakan adalah yuridis normatif dengan pendekatan perundang-undangan dan konseptual. Hasil penelitian menunjukkan bahwa secara teoritis prinsip S D bertujuan untuk mewujudkan keadilan bagi negara-negara berkembang. Hal ini sesuai dengan teori keadilan dari John Rawls bahwa justice as fairness dan Frank J Garcia dalam konteks perdagangan internasional. Berdasarkan teori tersebut SD menghendaki adanya pembedaan perlakuan antara negara-negara maju dengan negara sedang berkembang. Prinsip SD merupakan instrumen untuk tercapainya keadilan dalam perdagangan internasional. Dalam implementasinya, ketentuan SD yang ditujukan untuk membantu negara berkembang yang terdiri dari akses pasar, kepentingan negara berkembang yang dilindungi, fleksibilitas dan masa transisi sulit diterapkan karena negara-negara maju sering menggugat negara berkembang ke panel WTO ketika prinsip SD diterapkan.